Islamic Spiritual Well-Being as a Mediator in CRM–Loyalty Relationships: Evidence from Islamic Microfinance - Nurul Huda; Misnen Ardiansyah; Mukhamad Yazid Afandi (Business and Applied Management Journal, 2025)
This study examines the influence of Customer Relationship Management (CRM) on customer loyalty among Muslim members of Islamic microfinance institutions and investigates the mediating role of Islamic Spiritual Well-Being (ISWB). Grounded in the Stimulus–Organism–Response (S–O–R) framework and the Islamic moral economy perspective, the study explores how CRM can cultivate loyalty rooted in Islamic values within Baitul Maal Wat Tamwil (BMT), a community-based Islamic financial cooperative. A quantitative cross-sectional survey was conducted with 225 members of BMT Nahdlatul Ulama in Madura, Indonesia. ISWB was measured using a nine-item scale representing Islamic virtues such as Falah, Taqarrub, Itqan, Istiqamah, Ta’awun, Ikhlas, Akhlaq, Tawazun, and Qana’ah, while CRM and customer loyalty were measured using established scales. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4 and bootstrapping (5,000 resamples). The findings show that CRM significantly influences ISWB (β = 0.780, p < 0.001) and directly affects customer loyalty (β = 0.180, p < 0.05). ISWB also significantly enhances customer loyalty (β = 0.541, p < 0.001) and partially mediates the CRM–loyalty relationship (indirect β = 0.422), accounting for 70.1% of the total effect. These results highlight the importance of integrating Islamic values into CRM practices to strengthen spiritually grounded customer loyalty in Islamic financial institutions.